2007
DOI: 10.1029/2006ja012189
|View full text |Cite
|
Sign up to set email alerts
|

Statistical description of the bulge‐type auroral substorm in the far ultraviolet

Abstract: [1] Using global auroral images at ultraviolet wavelengths during 116 substorms, we have obtained quantitative measures of key features of the bulge aurora and oval aurora: their temporal variations, their locations, rates, and characteristics of gross expansion and decay, and the variability of these parameters. The expansion period identified solely from images varied primarily from 10 to 40 minutes, with an average of 30.9 minutes. To avoid mixing expansion data with recovery data, we normalized the time of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

17
127
4

Year Published

2009
2009
2015
2015

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(148 citation statements)
references
References 31 publications
(60 reference statements)
17
127
4
Order By: Relevance
“…Disturbances were classified as substorms, if they were accompanied by a poleward bulge expansion from the auroral oval near midnight and by the development of an auroral surge in the evening sector to the west of the bulge. Gjerloev et al (2007) found that the Akasofu type substorm is the predominant type of auroral events for isolated substorms. In 116 cases of all the selected events, the auroral disturbances developed according to the classical scheme of Akasofu (1964a), and only 20 further cases did not display the classical characteristics.…”
Section: Auroral Substormsmentioning
confidence: 99%
See 2 more Smart Citations
“…Disturbances were classified as substorms, if they were accompanied by a poleward bulge expansion from the auroral oval near midnight and by the development of an auroral surge in the evening sector to the west of the bulge. Gjerloev et al (2007) found that the Akasofu type substorm is the predominant type of auroral events for isolated substorms. In 116 cases of all the selected events, the auroral disturbances developed according to the classical scheme of Akasofu (1964a), and only 20 further cases did not display the classical characteristics.…”
Section: Auroral Substormsmentioning
confidence: 99%
“…21 proves to be the most complete generalisation about the conception of a single substorm development in the auroras and its description by Feldstein et al (2010). Gjerloev et al (2007) determined how often auroral manifestations of polar substorms occur according to the scheme shown in Fig. 20 (Akasofu, 1964a), but in a somewhat simplified manner.…”
Section: Auroral Substormsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this paper we investigate the evolution of the aurora during the growth, expansion, and recovery phases of substorms in a quantitative, statistical fashion. Previous workers have undertaken similar studies, for instance Mende et al (2003), Coumans et al (2007) and Gjerloev et al (2007), providing much insight into the average characteristics of the auroral evolution during substorms. However, our primary focus in this paper is to examine the role of the substorm in solar windmagnetosphere coupling, specifically in the closure of open flux previously accumulated through magnetic reconnection at the dayside magnetopause.…”
Section: Introductionmentioning
confidence: 99%
“…These techniques have included visual inspection (e.g., Elphinstone et al, 1990;Gjerloev et al, 2007), identifying a return to a threshold of low auroral luminosity poleward of the main emission (e.g., Brittnacher et al, 1999;Baker et al, 2000), identifying a return to a fraction of the peak intensity on the poleward edge of the main emission (e.g., Kauristie et al, 1999;Baker et al, 2000;Carbary et al, 2003;Boakes et al, 2008), and identifying a return to an intensity threshold relative to background intensity levels (e.g., Mende et al, 2003;Gjerloev et al, 2008). Carbary et al (2003) estimated over 23 000 poleward auroral luminosity boundaries (PALB) from images recorded by the ultraviolet imager (UVI) on the Polar satellite, by modelling latitudinal profiles of auroral luminosity intensity as a Gaussian function superimposed on a quadratic background.…”
Section: Introductionmentioning
confidence: 99%